2007
DOI: 10.1038/sj.npp.1301461
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effects of Cholinergic Modulation on Task Performance during Selective Attention

Abstract: The cholinergic neurotransmitter system is critically linked to cognitive functions including attention. The current studies were designed to evaluate the effect of a cholinergic agonist and an antagonist on performance during a selective visual attention task where the inherent salience of attended/unattended stimuli was modulated. Two randomized, placebo-controlled, crossover studies were performed, one (n ¼ 9) with the anticholinesterase physostigmine (1.0 mg/h), and the other (n ¼ 30) with the anticholiner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 54 publications
4
78
2
1
Order By: Relevance
“…However, in addition to results from our electrochemical recordings studies (18,19), a considerable literature on the effects of pharmacological manipulations of the cholinergic system on attentional performance in animals and humans (27)(28)(29) is consistent with the present attribution of a cholinergic mechanism underlying the effects of optogenetic stimulation on cue detection processes (as defined in the introduction).…”
Section: Discussionsupporting
confidence: 62%
“…However, in addition to results from our electrochemical recordings studies (18,19), a considerable literature on the effects of pharmacological manipulations of the cholinergic system on attentional performance in animals and humans (27)(28)(29) is consistent with the present attribution of a cholinergic mechanism underlying the effects of optogenetic stimulation on cue detection processes (as defined in the introduction).…”
Section: Discussionsupporting
confidence: 62%
“…PD patients with VH were found to have impaired attention and higher cortical visuoperception, due to prefrontal cortex and parietooccipital cortex dysfunction respectively on functional imaging [16][17][18][19], and higher Lewy body density and alpha-synuclein aggregation was found in prefrontal, temporal and visuoperceptive areas in patients with coexistent PD and VH than age matched controls without VH [20][21][22][23].…”
Section: Pathogenesis Of Visual Hallucinations In Parkinson's Diseasementioning
confidence: 99%
“…Low cholinergic activity following the use of anticholinergic drugs impairs attention [17,18] and visual processing [19], and can sometimes induce delirium with VH, even in individuals without clinical evidence of PD (Han et al, 2001) [20]. In contrast, use of cholinesterase inhibitors improves attention, thalamic function and visual processing in a dose-dependent manner [17,[21][22][23].…”
Section: The Role Of Acetylcholine Dopamine and Serotonin In The Devmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation due to AD -related drug mechanisms have also been investigated by using anticholinesterase physotigmine on healthy subject populations during tasks of working memory, emotion processing, visual attention and found that cholinesterase inhibitors may through modulation of activation in visual areas (increased) and frontal areas (decreased) lead to enhancement of stimulus processing and selectivity improve cognitive performance (Furey et al 2000;Bentley et al 2003;Bentley et al 2004;Furey et al 2008). In addition, similar approach has been utilized in studies comparing healthy subjects with AD patients during a visual attentional task where activation pattern was investigated during placebo and physotigmine-induced modulation of the activation (Bentley et al 2008).…”
Section: Clinical Drug Developmentmentioning
confidence: 99%